2019
DOI: 10.5194/se-10-1155-2019
|View full text |Cite
|
Sign up to set email alerts
|

Stress characterization and temporal evolution of borehole failure at the Rittershoffen geothermal project

Abstract: Abstract. In the Upper Rhine Graben, several innovative projects based on enhanced geothermal system (EGS) technology exploit local deep-fractured geothermal reservoirs. The principle underlying this technology consists of increasing the hydraulic performances of the natural fractures using different stimulation methods in order to circulate the natural brine at commercial flow rates. For this purpose, knowledge of the in situ stress state is of central importance to predict the response of the rock mass to di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…These results show that a common rupture with strike, dip and rake in the intervals 195 to 210° N, 85 to 90° and − 5 to 20°, respectively, could be attributed to the earthquakes associated with the stimulation operations, at least for the strongest ones. Interestingly, Azzola et al (2019) identified a maximal horizontal stress direction of N15° in the Buntsandstein, which is consistent with the observed strike range and the earthquake depths. The corresponding focal plane is relatively consistent with the earthquake distribution as well as the Rittershoffen fault orientation.…”
Section: Focal Mechanismssupporting
confidence: 84%
See 1 more Smart Citation
“…These results show that a common rupture with strike, dip and rake in the intervals 195 to 210° N, 85 to 90° and − 5 to 20°, respectively, could be attributed to the earthquakes associated with the stimulation operations, at least for the strongest ones. Interestingly, Azzola et al (2019) identified a maximal horizontal stress direction of N15° in the Buntsandstein, which is consistent with the observed strike range and the earthquake depths. The corresponding focal plane is relatively consistent with the earthquake distribution as well as the Rittershoffen fault orientation.…”
Section: Focal Mechanismssupporting
confidence: 84%
“…Second, the vertical distance to the injection point is relatively large, of the same order as the horizontal distance to the injection point. Such a development of seismicity is not in accordance with the expected normal-to strike-slip faulting regime of the region (Azzola et al 2019;Cornet et al 2007;Hehn et al 2016), which favors a horizontal (rather than vertical) extension of seismicity. Third, the observed vertical distribution does not follow the dip of the Rittershoffen fault and would require the presence of another fault that was not identified, neither from drilling logs nor from active seismic processing.…”
Section: Spatial Distributionmentioning
confidence: 92%
“…The dashed SV gradients in Fig. 9 are calculated on the base of density values of Rittershofen (Azzola et al, 2019) Valley and Evans (2007) show measured Shmin magnitudes between 1500 and 4500 m depth.…”
Section: Magnitudes Of Shmin Shmax and Svmentioning
confidence: 99%
“…Knowledge about the stress state in the upper crust is of great importance for many economic and scientific questions. For example, wellbore stability (Bell, 2003;Kristiansen, 2004), operation and stimulation of hydrocarbon and geothermal reservoirs (Altmann et al, 2014;Azzola et al, 2019;Henk, 2009;Smart et al, 2014), slip and dilation tendency of existing faults and fractures (Hettema, 2020;Konstantinovskaya et al, 2012), underground mining (Brady & Brown, 2004) or deep 30 tunnelling (Diederichs et al, 2004). Furthermore, it plays a decisive role in the search for a disposal site for high-level radioactive waste, since it is crucial for the short and long-term safety of a possible repository.…”
Section: Introductionmentioning
confidence: 99%
“…Because variations in normal traction along faults strongly influence dynamic rupture simulations (e.g., Kame et al, 2003;Duan and Oglesby, 2007;Lozos et al, 2012;Duan, 2019), we need to better constrain these tractions to produce more accurate earthquake simulations. Resolving the details of variable normal traction along faults requires additional data sets, such as detailed stress inversions from borehole breakouts (e.g., Azzola et al, 2019), focal mechanisms (e.g., Abolfathian et al, 2019), and mechanical models of stress state that consider heat flow, topography, and rheologic variations (e.g., Luttrell and Smith-Konter, 2017). The most likely future breakthroughs will come from utilizing a combination of approaches.…”
Section: Resolved Tractions Likely Oversimplify Initial Conditions Fomentioning
confidence: 99%